"Not easy, smooth, or automatic": Canada-US relations, Canadian nationalism, and American foreign policy, 1961--1963 - McKercher, Asa (University of Ottawa (Canada), 2009)
An historical consensus has coalesced around the view that Canadian-American relations reached a nadir from 1961-1963. The argument is that due to differences of both personality and policy John Diefenbaker, Canada's Prime Minister, and US President John Kennedy loathed each other. Scholars have subsequently debated over who was more to blame for this, but their analyses have been incomplete because the American side has largely been ignored. As most, if not all, of the historians who have examined the Diefenbaker-Kennedy era have been Canadian, American archival sources have been used sparingly. Drawing upon the rich documentary collection in the US National Archives and the Kennedy Presidential Library, this thesis argues, in contrast to what many have contended, that US foreign policy was in fact quite complimentary towards Diefenbaker's government. This was primarily because American policy-makers were aware of the potent force of Canadian nationalism, which their experiences with Diefenbaker only confirmed.
Keywords: History, Canadian.; History, United States.; History, Modern.; Political Science, International Relations.